Influence of COVID-19 infection on early pregnancy outcomes in different periods around frozen embryo transfer - Yiling Ko; Luting Chen; Chengliang Zhou; Ji Xi; Yu Xiao; Xiaojun Chen (BMC, 2024)
Abstract Purpose The study aimed to investigate the potential influence of COVID-19 infection on embryo implantation and early development in women undergoing frozen embryo transfer (FET), with a specific focus on infections occurring at different periods around FET. Methods A retrospective analysis was performed on women who had undergone FET during a period marked by a significant surge in COVID-19 infection in Shanghai. All enrolled women experienced their first documented COVID-19 infection around the time of FET, ensuring that infections did not occur prior to oocyte retrieval. Participants were categorized into six groups based on the timing of infection: uninfected, ≥ 60 days, < 60 days before FET, 0-14 days, 15-28 days, and 29-70 days after FET. Clinical outcomes were compared across these groups. Results The infection rate among the total of 709 cases was 78.28%. Infected individuals exhibited either asymptomatic or mild symptoms. The ongoing pregnancy rates for the first four groups were 40.7%, 44.4%, 40.5%, and 34.2% (P = 0.709) respectively, biochemical pregnancy rates (59.1% vs. 61.1% vs. 67.6% vs. 55.7%, P = 0.471) and clinical pregnancy rates (49.6% vs. 55.6% vs. 55.4% vs. 48.1%, P = 0.749), all showed no significant differences. Early spontaneous abortion rates across all six groups were 18.3%, 20.0%, 25.0%, 28.9%, 5.4%, and 19.0% respectively, with no significant differences (P = 0.113). Multivariable logistic analysis revealed no significant correlation between the infection and ongoing pregnancy. Conclusion Asymptomatic or mild COVID-19 infections occurring around FET do not appear to have a significant adverse impact on early pregnancy outcomes.